An Analysis of Students English Learning Reading Strategy in HOTS Text At Second Grade SMAN 3 Batusangkar - M. Fachrul Anshar; Pami Putri, Hilma; Prima Dewi, Merry; Sakti, Genta (Yayasan Lembaga Studi Makwa, 2022)
This research was motivated by the problems of class XI students at SMAN 3 Batusangkar. Some students have limitations in the knowledge of correct reading learning strategies, which causes some problems for students in writing. First, some students have various reading strategies that make these students have problems in learning. Second, some students do not understand the use of good and correct learning strategies in discussing HOTS questions. The researcher's question in this study is what are the students' strategies in learning reading and how they use them. The purpose of this research is to find out what types of strategies students have in learning reading and how they use them. This study uses mixed research methods with class XI as the research population. The research sample amounted to 40. Data was collected through open and closed questionnaires. In a closed questionnaire, students are asked to tick one of the scales containing 3 scores. In an open questionnaire, the researcher got the answers what the students' strategies were and how they implemented them. The results showed that most of the students applied a strategy based on the highest percentage, the strategy was a cognitive strategy of 10.3% and the lowest percentage was an affective strategy of 6.57% in using the HOTS text reading strategy. Researchers can conclude as follows. First, students use cognitive strategies because they help students make up for their lack of knowledge in learning to read. Second, most students rarely use affective strategies for several reasons in reading HOTS texts. Abstrak Penelitian ini dilatarbelakangi oleh permasalahan siswa kelas XI SMAN 3 Batusangkar. Beberapa siswa memiliki keterbatasan dalam pengetahuan strategi pembelajaran membaca yang benar, yang menyebabkan beberapa masalah bagi siswa dalam menulis. Pertama, beberapa siswa memiliki berbagai strategi membaca yang membuat siswa tersebut memiliki masalah dalam belajar. Kedua, sebagian siswa belum memahami penggunaan strategi pembelajaran yang baik dan benar dalam membahas soal HOTS. Pertanyaan peneliti dalam penelitian ini adalah apa strategi siswa dalam belajar membaca dan bagaimana mereka menggunakannya. Tujuan dari penelitian ini adalah untuk mengetahui jenis strategi apa yang dimiliki siswa dalam pembelajaran membaca dan bagaimana mereka menggunakannya. Penelitian ini menggunakan metode penelitian campuran dengan kelas XI sebagai populasi penelitian. Sampel penelitian berjumlah 40. Data dikumpulkan melalui kuesioner terbuka dan tertutup. Dalam angket tertutup, siswa diminta mencentang salah satu skala yang berisi 3 skor. Dalam angket terbuka, peneliti mendapat jawaban apa strategi siswa dan bagaimana mereka menerapkannya. Hasil penelitian menunjukkan bahwa sebagian besar siswa menerapkan strategi berdasarkan persentase tertinggi yaitu strategi kognitif sebesar 10,3% dan persentase terendah adalah strategi afektif sebesar 6,57% dalam menggunakan strategi membaca teks HOTS. Peneliti dapat menyimpulkan sebagai berikut. Pertama, siswa menggunakan strategi kognitif karena membantu siswa menutupi kekurangan pengetahuan mereka dalam belajar membaca. Kedua, sebagian besar siswa jarang menggunakan strategi afektif karena beberapa alasan dalam membaca teks HOTS.